From Railroad to Highway: Shifting Use of Land Transportation System in the Northern Coast of Central Java - Hartatik, Endah Sri (History Department, Semarang State University and Historian Society of Indonesia, 2019)
The development of land transportation facilities both trains and highway in the end of 19th and 20th century was closely related to the production plantation crops. Historical method was used in writing this article. Documentation was done by searching information related to road accidents. Documents would be traced in Jakarta National Archives, Jakarta National Library, Press Monument in Surakarta, Central Bureau of Statistics Central Java, several libraries in Yogyakarta. In early 20th century, trains became a main transportation system because they might transport plantation crops in large quantities before drove in the port city. However, due to the decline in plantation production, the function of trains decreased as well. During the New Order era which focused on agrarian farming system, trainsÃ¢â‚¬â„¢ function as transportation went down and replaced by highway. In other words, highway became a primary transportation system because they were able to transport production crops (e.g. rice) from fields to our house. This shifting use was closely related to the policy issued by the government.Ã‚Â Pengembangan fasilitas transportasi darat baik kereta api maupun jalan raya pada akhir abad ke-19 dan ke-20 terkait erat dengan produksi tanaman perkebunan. Metode historis digunakan dalam menulis artikel ini. Dokumentasi dilakukan dengan mencari informasi terkait kecelakaan di jalan. Dokumen akan dilacak di Arsip Nasional Jakarta, Perpustakaan Nasional Jakarta, Monumen Pers di Surakarta, Biro Pusat Statistik Jawa Tengah, beberapa perpustakaan di Yogyakarta. Pada awal abad ke-20, kereta api menjadi sistem transportasi utama karena mereka mengangkut tanaman perkebunan dalam jumlah besar sebelum melaju di kota pelabuhan. Namun, karena penurunan produksi perkebunan, fungsi kereta api juga menurun. Selama era Orde Baru yang berfokus pada sistem pertanian agraria, fungsi kereta api sebagai transportasi turun dan digantikan oleh jalan raya. Dengan kata lain, jalan raya menjadi sistem transportasi utama karena mereka dapat mengangkut tanaman produksi (misalnya beras) dari ladang ke rumah. Pergeseran penggunaan ini terkait erat dengan kebijakan yang dikeluarkan oleh pemerintah.Ã‚Â